Mengelolah Konflik terhadap Lembaga - Ahmad Rojali (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2020)
Conflict is inevitable in an organization (the Institute) this is caused by many factors which in essence because the organization is made up of many individuals and groups who certainly has the nature and objectives are different from each other. Conflict is not always negative impact but could also lead to a positive impact. In any conflict occurs because of several factors induvidu differences, differences in cultural backgrounds, different interests, as well as rapid and sudden changes in society. Any problems or conflicts certainly have a strategy in handling them perform the competition, sharing, accommodation, collaboration and avoidance. Conflicts can be resolved depends on how we manage that conflict does not escalate into a disadvantage however would be a positive thing for the organization.